Patients Receiving Correctional Assistance At Class 1 Rutan Clinic In Central Jakarta's Knowledge Of Covid-19 Prevention And Review From An Islamic Perspective - Amara Nurul Afifah; Edward Syam; Muhammad Arsyad (Junior Medical Journal, 2022)
Background: A novel variety of coronavirus is what causes Coronavirus Sickness-2019 (Covid-19), a disease. Cough, fever, exhaustion, breathlessness, and lack of appetite are signs of the Covid-19 infection. In order to prevent the corona virus from spreading further, the WHO refers to physical separation as a physical distance regulation. To be able to stop the spread of COVID-19, research on COVID-19 awareness among patients receiving correctional assistance at the Class 1 Rutan Clinic in Central Jakarta is deemed crucial.Method: This kind of study employs cross-sectional research methodology and descriptive observation. 2,900 patients receiving correctional assistance made up the study's sample of 352 participants, who were seen at the Class 1 Rutan Clinic in the heart of Jakarta. Techniques for gathering data include surveys and one-on-one interviews with respondents. Bivariate and univariate analysis are the methods used in this study.Result: Features of the 352 respondents, including 89 (25.28%) respondents who were between the ages of 24 and 29. As many as 281 (79.8%) respondents reported that they had never heard of COVID-19. 66% of the 233 respondents have high knowledge and preventative skills. There is a correlation between the Knowledge Level of Prevention and the Incidence of COVID-19, according to the findings of the Chi-Square statistical test, which yielded the Continuity Correction value = 0.049 where p0.05.Conclusion: The Class 1 Central Jakarta Rutan Clinic classifies the level of COVID-19 prevention knowledge among patients receiving correctional assistance as "excellent." The incidence of COVID-19 in patients treated at the Class 1 Rutan Clinic in Central Jakarta is correlated with knowledge and prevention. According to the Islamic perspective, the Messenger of Allah discouraged people from entering areas where the plague was rife and from attempting to flee the plague.